Análise hidrodinâmica de um sistema de desinfecção de ar por UV-C - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
On March 11, 2020, the new coronavirus pandemic (SARS-coV-2) was declared by the World Health Organization (WHO) and thus, causing the paralysis of federal institutions, including UFOPA. COVID 19 is a disease with a high transmission rate, both through direct contact between people, for example, droplets expelled when coughing or sneezing, or through indirect contact, such as through air circulation in closed environments. To prevent the spread of the virus, it was recommended and later mandatory, to wear a mask and social distance. To reduce the risks of contagion and spread of COVID-19 at the university, an air disinfection system was developed using germicidal ultraviolet irradiation technology. Therefore, the present work aims to present the hydrodynamic analysis of an air disinfection system using UV-C radiation, having asimportant flow parameters: speed profile, pressure loss, friction factor, radiation dosage, time of radiation exposure and intensity, depending on the geometric characteristics of the disinfection system.
Keywords: Análise Hidrodinâmica; Desinfecção de ar; Covid-19; Radiação UVC; CNPQ:: ENGENHARIAS